Tolosa-Hunt syndrome. The dangers of an eponym. Issue 3 (March 1975) - Fowler, T. J.; Earl, C. J.; McAllister, V. L.; McDonald, W. I.
Abstract : Two cases of painful ophthalmoplegia are described which were initially thought to be examples of the Tolosa-Hunt syndrome. Both were partially responsive to steroid treatment. Subsequent investigations showed that in one case the condition was due to an aneurysm and in the other to a malignant lymphoma.